2005
DOI: 10.1093/sleep/28.1.123
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Use of the MSLT and MWT

Abstract: The studies examined in this review indicate that the MSL is sensitive to conditions expected to increase sleepiness. MSL are generally lower following sleep loss, following use of sedating medications, during wakefulness in the late night or early morning hours, and among patients with sleep disorders associated with excessive sleepiness such as narcolepsy or obstructive sleep apnea. However, the wide range in MSL makes it difficult to establish a specific threshold value for excessive sleepiness or to discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
236
2
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(255 citation statements)
references
References 100 publications
7
236
2
10
Order By: Relevance
“…The SOL is measured from lights out to the first minute of stage 1 sleep. Significant correlations often found between the length of sleep loss and sleep latency gives face validity for using sleep onset latency as a biologically based measure of sleepiness (Arand, Bonnet, Hurwitz, Mitler, Rosa, & Sangal, 2005).…”
Section: Sleep Onset Latency (Sol)mentioning
confidence: 99%
“…The SOL is measured from lights out to the first minute of stage 1 sleep. Significant correlations often found between the length of sleep loss and sleep latency gives face validity for using sleep onset latency as a biologically based measure of sleepiness (Arand, Bonnet, Hurwitz, Mitler, Rosa, & Sangal, 2005).…”
Section: Sleep Onset Latency (Sol)mentioning
confidence: 99%
“…The morning after the overnight PSG, patients underwent MSLT. 4 The mean sleep latency of each of the four or five naps and whether REM sleep was observed were reported.…”
Section: Objective Measures Of Sleepmentioning
confidence: 99%
“…1-3 Excessive sleepiness is defined as sleepiness occurring in a situation when an individual is expected to be awake and alert. 4 Fatigue is defined as a subjective lack of physical or mental energy that is perceived by the individual or caregiver to interfere with usual and desired activities. 5 Sleepiness and fatigue, although often occurring in the same patient, can exist independently, and either can negatively impact quality of life in MS. 3 The etiology of these symptoms has not been completely elucidated, although studies have shown that sleep disturbances are associated with a higher incidence of fatigue and daytime sleepiness.…”
mentioning
confidence: 99%
“…However, this test has undergone further tests of validity, and the test is criticized for lack of a standardized protocol. 10,11 …”
Section: Maintenance Of Wakefulness Testmentioning
confidence: 99%
“…MSLT criteria for narcolepsy are: mean sleep latency shorter than 5 minutes or 2 or more REM episodes in five naps. 10,11,13 …”
Section: Narcolepsymentioning
confidence: 99%